Small business lending and social capital: Are rural relationships different? - Robert DeYoung; Dennis C. Glennon; Peter J. Nigro; Kenneth Spong (The Journal of Entrepreneurial Finance (JEF), 2019)
We test whether rural versus urban location, and the amount of social capital present in those locations, influence the performance of Small Business Administration (SBA) 7(a) loans originated between 1984 and 2012. On average, we find that rural loans are about 11% less likely to default than urban loans, and that a standard deviation increase in social capital reduces default by about 5%. Surprisingly, these two effects are largely independent of each other, even though social capital is substantially higher in rural places than in urban places. Our findings advance the small business lending literature and offer insights for a more efficient allocation of SBA funds.
Keywords: G21; R0; G28; 650; Commercial banks; Rural lending; Small business loans; Social capital; SBA